TUJUAN BERIBADAH KEPADA TUHAN BERDASARKAN MAZMUR 63:2-5 DAN IBRANI 10:25 - Trisno Kurniadi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2015)
The term worship is no stranger to believers. But now there are many shifts to the motivation and purpose of worship. Worship aimed at worshiping the Triune God has now been diverted for the purposes of human emotionality. The psalmist and writer of the Hebrews stressed the importance of understanding the purpose of worship. In this article we will discuss